2008
DOI: 10.3748/wjg.14.5900
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the Chinese literature for the treatment of achalasia

Abstract: AIM:To evaluate the effect of different approaches in the treatment of achalasia in China. METHODS:We performed a systematic review and meta-analysis of Chinese literature by searching the Chinese Biomedical Database and Chinese scientific Journals database (up to March 2008). All cohort studies (controlled or uncontrolled) in which the patients were observed for more than a year were reviewed in detail. Dichotomous outcomes were reported as relative risks (RR) with 95% confidence interval (CI) for controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…Two recent meta-analyses concluded that botulinum toxin injection in patients with achalasia had an excellent safety profile but was slightly less effective than pneumatic dilatation in the short-term and clearly inferior in the longterm [23,24]. Of note, a randomized, controlled trial has shown that the two currently commercially available formulations of botulinum toxin are equally effective but need to be given in different dosages because of variable potency [25].…”
Section: Botulinum Toxin Injectionsmentioning
confidence: 96%
“…Two recent meta-analyses concluded that botulinum toxin injection in patients with achalasia had an excellent safety profile but was slightly less effective than pneumatic dilatation in the short-term and clearly inferior in the longterm [23,24]. Of note, a randomized, controlled trial has shown that the two currently commercially available formulations of botulinum toxin are equally effective but need to be given in different dosages because of variable potency [25].…”
Section: Botulinum Toxin Injectionsmentioning
confidence: 96%
“…A meta-analysis of controlled and uncontrolled studies in the Chinese literature (43 articles with 1791 participants) also showed that myotomy was associated with higher initial and long-term remission rates than pneumatic dilation or botulinum toxin injection. Only 2 studies compared open myotomy with laparoscopic myotomy; there was no difference in remission rate [39] . Since results after any treatment may deteriorate over time, life-long follow-up and objective assessment of the results are recommended.…”
Section: Treatmentmentioning
confidence: 99%
“…More recently, laparoscopic and thoracoscopic techniques have been used to perform myotomy [39,[44][45][46] . The modified Heller approach results in good to excellent relief of symptoms in 70% to 90% of patients with few serious complications.…”
Section: Surgical Myotomymentioning
confidence: 99%
“…The advantages of balloon dilatation include shorter length of stay, quicker recovery time, and decreased cost [13] . Pneumatic dilatation can be complicated by substernal pain, prolonged epigastric pain, esophageal perforation, aspiration pneumonia, and GERD [13,[16][17][18][19] . Multiple studies suggest that in older children, pneumatic dilation is effective and safe initial treatment for achalasia and may spare children with achalasia an operation [13,14,20] .…”
Section: Pneumatic Dilatationmentioning
confidence: 99%